PENGARUH VARIASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK JAZZMYN NATURAL - Muthiah, Meidina; Mariah , Mariah (Journal of Development Economics and Digitalization, Tourism Economics, 2025)
Jazzmyn Natural is a spray deodorant product that is popular with many people, therefore there has been an increase in sales of this deodorant product, since it was announced that there is a bar product, buyers are increasingly interested in Jazzmyn deodorant. This research aims to assess the impact of differences in product variety and product quality on purchasing patterns for Jazzmyn products. The research method used is a quantitative approach. The target population is consumers who have purchased or will purchase Jazzmyn products, with a total sample of 285 respondents selected using the Slovin sampling technique. To collect data and information to support research, the methods used include observation, distributing questionnaires, and reviewing literature. The results of the research show that product variations have a partially significant positive influence on purchasing decisions for Jazzmyn products. Meanwhile, product quality also has a partial positive influence on purchasing decisions for that product. Furthermore, both product variety and product quality have a positive and significant impact simultaneously on purchasing decisions for Jazzmyn deodorant products.